GRAMMAR GAMES AND MOTIVATION: EXPLORING THE LINK BETWEEN ENJOYMENT AND RETENTION OF GRAMMATICAL STRUCTURES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study investigates the role of grammar games in enhancing primary school learners’ motivation and retention of English grammatical structures. Employing a mixed-methods quasi-experimental design with 60 intermediate EFL learners, the study compares the effects of game-based grammar instruction versus traditional teaching methods. Quantitative results reveal significantly higher grammar retention and motivation in the game-based group. Qualitative data from interviews and learner journals highlight increased enjoyment, confidence, and peer collaboration through games. The findings underscore the effectiveness of integrating grammar games into language instruction to foster both cognitive and affective learning outcomes. Implications for teaching practice and future research are discussed.